CENTRAL NERVOUS SYSTEM TUMORS: A HOSPITAL BASED ANALYSIS - Ayaz, Bushra; Lodhi, Faisal Rashid; Hasan, Mehmood (Pakistan Armed Forces Medical Journal, 2011)
Objective: To assess the spectrum of CNS tumors and provide benchmark data for future studies assessing data in continuum. Study Design: Descriptive study. Place and duration of study: This study was carried out from Jan 2003 till Jan 2009 at Pakistan Naval Ship Shifa (Naval Hospital) Karachi, Pakistan. Patients and Methods: One hundred cases fulfilling the inclusion criteria were included between the ages of 1-85 years belonging to both genders. Results: Majority of the cases were seen in the year 2008 with the most commonly encountered lesion being the glial tumors followed by the meningiothelial neoplasms. Our findings were similar to previous similar studies in our setup with little change in trends. Conclusion: Glial tumors appear to be more common in our setup whereas the popularly believed Meningiothelial tumors though common came next. Our study can form the benchmark data upon which future studies can be conducted.